How Innovation Does Influence Ethical Entrepreneurship (50%) Business Plan: ALDURA (50%) - ALI, ZALINA (2013)
Recently, the relationship between ethics and innovation is an avenue ripe for further inquiry and analysis. The aim of this study was to contribute to a better understanding of how entrepreneurs perceive ethics in this business in relation to technology and innovation and what would be their moral implications from any creative destruction scenario because pain and pleasure are the main principle in moral values (Wood et al, 2002). A conceptual framework consisting of three key elements is introduced to describe its relationships with entrepreneurial ethics over time. The three independent variables are perceived to influence the entrepreneurial ethics and engage in ‘creative destruction’ during the entrepreneurial innovation process because it is vital to sustain their business. Through a conversational analysis of this study, the findings suggest that entrepreneurial ethics comprise sets of the Entrepreneurs’ Personal Qualities as a leader in driving innovation; Global Forces of Technology, Innovation in developing a knowledge-driven culture of the company; and Instilling Shared Services for market improvement and sustainability in relation to innovation align with the conceptual framework aspired in this study. Though innovation and ethics are perceived as two different subjects by the entrepreneurs interviewed in this study, it is vital to ensure that entrepreneurs innovate ethically while adopting the latest technology development; simultaneously creating shared value in gaining positive growth sustainably. Discussions are drawn from the results, and priorities are established for future research.